A Rare Case of Fungal Necrotising Otitis Externa Centred on the Left Temporomandibular Joint - A. Khan; E. Omakobia; S. Hasnie; R. Barton; P. Gopalan; V. Oktseloglou; I. Smith (Case Reports in Otolaryngology)
Introduction. Necrotising otitis externa (NOE) is a rare life-threatening complication of simple otitis externa which can be difficult to diagnose and manage. It is very rarely centred on the temporomandibular joint (TMJ). Fungi cause NOE in approximately 5–20% of patients, and a high index of suspicion is required for diagnosis, particularly when there is no improvement with prolonged topical and intravenous antibiotic therapy. Objective. To report a novel case of fungal NOE centred on the left TMJ in an immunocompromised adult male with a focus on investigations and optimal management. Case Report. A 67-year-old male with comorbid chronic renal impairment presented to our otolaryngology department with prolonged left otalgia and otorrhoea. Subsequent cross-sectional imaging demonstrated left NOE centred on the TMJ. Poor resolution with prolonged courses of systemic and topical anti-pseudomonal antibiotics prompted maxillofacial surgical input for left TMJ exploration, washout, and biopsy from the joint capsule. The causative organism was identified as Aspergillus flavus on PCR analysis. The patient was successfully treated with oral posaconazole and repeated topical insertions of amphotericin B-soaked ribbon gauze to the left ear. Discussion. A combination of various imaging modalities including CT, MRI, Tc-99, and gallium-67 are utilised in clinical practice both to diagnose NOE and subsequently monitor disease progression or resolution. Immunocompromised patients with confirmed fungal NOE may require a combination of treatments including surgical debridement and prolonged antifungal therapy for a number of months, if not lifelong, treatment. Initiating empirical antifungal therapy may be justified in some patients. However, this should be judged on a case-by-case basis and guided by discussion with the local microbiology and infectious diseases departments. However, there is no national guideline or consensus regarding treatment of these patients, especially in cases of fungal NOE.